Synergy of Public Administration and Education in Efforts to Improve the Quality of Education in Indonesia - Hidayat, Hidayat (Asosiasi Ahli Administrasi Indonesia, 2024)
Education plays a central role in developing superior and competitive human resources. However, challenges in improving the quality of education remain significant, including unequal access, inadequate infrastructure, and uneven distribution of educators. This research aims to identify the role of public administration in the education sector, explore the ideal synergy between public administration and education, and formulate strategies for enhancing educational quality. A literature review approach is used to analyze the synergy between public administration and education in improving educational quality in Indonesia. The sources of literature include scholarly journal articles, reports from educational institutions, government policies, and statistical data from official agencies. The research findings indicate that the synergy between public administration and education is crucial for enhancing educational quality. The ideal synergy involves effective coordination between central and local governments, as well as the involvement of the private sector and the community. Strategies for improving educational quality through inter-agency cooperation include collaboration between educational institutions and the government, networking among schools, developing teacher training, providing access to technology, conducting joint research, and implementing supervision. Recommendations from this research include increasing regional involvement in policy formulation, enhancing oversight, and strengthening partnerships with the private sector.